Normal Mouth Opening in an Adult Indian Population - Khare, Nishant (Springer-Verlag, 2012)
BACKGROUND: Mouth opening among different population has been shown to vary considerably and its range is specific for a given population. The present study is an attempt to calculate the normal mouth opening in adult Indian population. METHOD: A total of 894 adults, 463 males and 431 females, in the age range of 21 to 70 years were studied. The subjects were asked to open their mouth maximally till no further opening was possible. The distance from the incisal edge of the upper incisor teeth to the incisal edge of the lower incisor teeth was measured using a calibrated fiber ruler. To determine correlation of mouth opening with age a Pearson correlation analysis was performed and statistical significance was tested by the application of t test. OBSERVATIONS: The mean maximal mouth opening for males was 51.3 mm (SD 8.3) (Range 39–70 mm). The mean maximal mouth opening for females was 44.3 mm (SD 6.7) (Range 36–56 mm). There was significant difference between the mouth opening of male and female in all the age groups with P value <0.05. A linear relationship was observed between the mouth opening and age in both males and females and the mouth opening decreased as the age increased. CONCLUSION: The mean maximal mouth opening for Indian males is 51.3±8.3 mm and for females is 44.3±6.7 mm. The mouth opening seems to decrease with age. The mouth opening of females is significantly less than the males in all the age groups.